TAMAN WISATA SURYA FAM’S SEBAGAI DESTINASI PARIWISATA TEMATIK DI KABUPATEN KUANTAN SINGINGI - Sejati, Nurti Citra Purti; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Thematic tourism has become a trend in tourism today. This type of tourism is the answer to the needs of the community to travel, especially in areas that have limited tourist attractions. The development of thematic tourism areas can be an alternative for areas located far from famous tourist attractions, such as in Kuantan Singingi Regency. The activities carried out by tourists while at the location are a form of activity that revives tourism in this area. Thematic tourism is a type of tourism that organizes trips with a certain theme, narrative, or story so as to provide important experiences and lessons in tourism activities. This study aims to determine: 1) the variety of attractions available at Surya Fam's Tourism Park as a thematic tourist destination in Kuantan Singingi Regency; 2) the form of thematic tourism carried out at Surya Fam's Kuantan Singingi Tourism Park. The method used is a qualitative method with a descriptive approach, where researchers try to describe the actual conditions and circumstances by collecting data and information in the field. Based on the results of the study, this Tourism Park provides various photo spots with a flower garden background, a swimming pool, hanging bike, flying fox and gazebo are available. In general, Surya Fam's Tourism Park is themed Attractions theme parks with the main concept of family tourism. This type of theme is strengthened by the types of attractions and tourism activities displayed. Keywords: thematic tourism, attraction, family tourism